Synthesis, structure characterization and biological evaluation of new 6,8-dichloro-2-methyl-4H-chromen-4-one derivatives - Salem, Marwa Sayed; Marzouk, Magda Ismail; Ali, Salma Nasser; Madkour, Hassan Mohamed Fawzy (European Journal of Chemistry, 2012)
The typical active methyl functionality of 6,8-dichloro-2-methyl-4H-chromen-4-one is utilized to obtain 2-styrylchromones, pyruvate ester and phthalide via reactions with aromatic carboxaldehydes, diethyl oxalate and phthalic anhydride respectively. The phthalide provides illustrative example to convert a heterocyclic compound to an aliphatic one via the effect of alcoholic sodium methoxide. Bromination and cycloaddition reactions of 2-styrylchromones afford vicinal dibromide and adducts respectively. This work presents to the art a typical example of heterocyclic systems transformations through the conversion of the starting chromone to coumarin under the influence of thionyl chloride followed by aqueous potassium hydroxide. Some heterocyclic systems like pyrazole, isoxazol and quinolinone are obtained from the target chromone by treatment with hydrazines, hydroxylamine hydrochloride and ammonium acetate respectively. Thiation of starting chromone interestingly affords a dithiated product instead of the expected monothiated one. Antibacterial and antifungal activities of some synthesized compounds have been screened.